IMPLEMENTASI MINI MARKET PROJECT BERBASIS UMBI-UMBIAN DALAM PEMBELAJARAN IPS UNTUK MENDUKUNG SDGs 3 DAN 4 - Putri Shufania, Isabella; Wahyuningsih, Yona; Mulyana, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Mini Market Project, which utilises tubers, in teaching the subject of buying and selling in Year 4 of primary school, as well as examining the use of Sustainable Development Goals (SDGs) 3 and SDGs 4 in its implementation. The study used a qualitative descriptive approach with data collection techniques including observation, interviews, questionnaires, and documentation. The results of the study show that the implementation of the Mini Market Project runs systematically in accordance with the learning plan and involves students actively in every stage of the activity, from production to practical sales. Using tubers as production materials provides a contextual learning experience and promotes awareness of the importance of healthy eating habits as part of the implementation of SDGs 3. Furthermore, the project-based learning approach implemented was able to increase the participation, creativity, and collaboration of the students, thus supporting the realisation of quality education as reflected in SDGs 4. The students' response to the learning process indicates a positive trend, where learning becomes more engaging, enjoyable, and meaningful. Therefore, the implementation of the Mini Market Project based on the utilisation of tubers can be an alternative form of contextual and integrative learning to develop understanding of concepts, as well as forming the skills and attitudes of students.